2018
DOI: 10.1186/s13046-018-0827-y
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Ras-related protein 1A promotes an aggressive phenotype in colorectal cancer via PTEN/FOXO3/CCND1 pathway

Abstract: BackgroundColorectal cancer (CRC) is a commonly diagnosed digestive malignancy worldwide. Ras-related protein 1A (RAP1A) is a member of the Ras superfamily of small GTPases and has been recently identified as a novel oncoprotein in several human malignancies. However, its specific role in CRC remains unclear.MethodIn this study, we firstly analyzed its expression and clinical significance in a retrospective cohort of 144 CRC patients. Then, cellular assays in vitro and in vivo were performed to clarify its bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…PTEN (Phosphatase and tensin homolog deleted on chromosome 10) consists of 9 exons and encodes protein-containing 403 amino acids with phosphatase activity [9]. PTEN functions as an important regulator in PI3K/protein kinase B (AKT) signaling pathway for inflammatory diseases [10,11] and is also responsible for angiogenesis, cell survival and other biological processes [12]. Importantly, accumulating evidence has indicated the crucial role of PTEN in sepsis-induced diseases.…”
Section: Introductionmentioning
confidence: 99%
“…PTEN (Phosphatase and tensin homolog deleted on chromosome 10) consists of 9 exons and encodes protein-containing 403 amino acids with phosphatase activity [9]. PTEN functions as an important regulator in PI3K/protein kinase B (AKT) signaling pathway for inflammatory diseases [10,11] and is also responsible for angiogenesis, cell survival and other biological processes [12]. Importantly, accumulating evidence has indicated the crucial role of PTEN in sepsis-induced diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Forkhead box O3 (FOXO3) belongs to the O subclass of the forkhead family of transcription factors and is a well-established tumor suppressor 18 . FOXO3 has been shown to control various aspects of breast cancer biology 1921 . Song et al 19 reported that restoration of FOXO3 induces apoptosis and cell cycle arrest and reverses 5-fluorouracil resistance in human breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Sisci et al 20 demonstrated that overexpression of FOXO3 decreases migration, invasion, and anchorage-independent growth of estrogen receptor α-positive breast cancer cells. Multiple target genes such as CCND1 and VEGF have been proposed to mediate the anticancer activity of FOXO3 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…It encodes a protein 403 amino acids in length and has phosphatase activity (30). It has been reported that PTEN is able to inhibit the development of tumors by antagonizing tyrosine kinase and other phosphorylases responsible for angiogenesis, cell survival and other biological processes (31). PTEN is also associated with the PI3K/protein kinase B (AKT) signaling pathway (32).…”
Section: Introductionmentioning
confidence: 99%